Integrative Model of Human Resource Management Based on Maqasid al-Syari'ah and Its Impact on Organizational Performance in Sharia Financial Institutions in Region III Cirebon - Aris Budiman; Abdul Aziz; Anton Bawono; Wartoyo; Layaman (Lembaga Bale Literasi, 2026)
In this paper, I explore an integrative model of Human Resource Management (HR) based on the principles of Maqasid al-Syari'ah and its impact on organizational performance in Sharia Financial Institutions in Indonesia. I begin by emphasizing the relevance of Maqasid al-Syari'ah, which aims to preserve religion, life, intellect, heredity, and wealth, in order to improve the practice of human resources. My research addresses gaps in the existing literature regarding the integration of these principles into HR frameworks. Using a mixed-methods approach, I analyzed data collected from various Sharia Financial Institutions in Region III Cirebon, evaluating how Maqasid al-Shari'ah-based HR strategies, such as ethical hiring and employee development, contribute to improving organizational performance metrics. The findings demonstrate the benefits and challenges of implementing this model, offering valuable insights into improving employee satisfaction and organizational productivity while adhering to Islamic values. In addition, I provide recommendations for future research and practical applications to further refine this integrative model.